Measurement of the top quark mass in the tt [bar] [right arrow] lepton+jets channel from √s=8 TeV ATLAS data and combination with previous results - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Jongmanns, Jan; Kolb, Mathis; Kugel, Andreas; et al. (The European physical journal. C, Particles and fields, 2019)
The top quark mass is measured using a template method in the tt¯→lepton+jetstt¯→lepton+jetst\bar{t} → lepton+jets channel (lepton is e or μμμ ) using ATLAS data recorded in 2012 at the LHC. The data were taken at a proton-proton centre-of-mass energy of s√=8s=8{\sqrt{s}} =8 TeVTeV\text {TeV} and correspond to an integrated luminosity of 20.220.220.2 fb−1−1^{-1}. The tt¯→lepton+jetstt¯→lepton+jetst\bar{t} → lepton+jets channel is characterized by the presence of a charged lepton, a neutrino and four jets, two of which originate from bottom quarks (b). Exploiting a three-dimensional template technique, the top quark mass is determined together with a global jet energy scale factor and a relative b-to-light-jet energy scale factor. The mass of the top quark is measured to be mtop=172.08±0.39(stat)±0.82(syst)mtop=172.08±0.39(stat)±0.82(syst)m_{top} =172.08 \,± \,0.39 \,(stat)\,± \,0.82 \,(syst) GeVGeV\text {GeV}. A combination with previous ATLAS mtopmtopm_{top} measurements gives mtop=172.69±0.25(stat)±0.41(syst)mtop=172.69±0.25(stat)±0.41(syst)m_{top} = 172.69 \,± \,0.25 \,(stat)\,± \,0.41 \,(syst) GeVGeV\text {GeV}.
ATLAS Collaboration: M. Aaboud, C.F. Anders, V.Andrei, C. Antel, A.E. Bolz, O. Brandt, M. Dunford, D.E. Ferreira de Lima, S. Franchino, J. Jongmanns, M. Kolb, A. Kugel, H. Meyer Zu Theenhausen, F. Napolitano, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S.M. Weber, M. Wessels, X. Yue [und weitere]
Gesehen am 01.08.2019